PENERAPAN APE SENSORY PATH DALAM MENINGKATKAN KETRAMPILAN MOTO- RIK KASAR ANAK KELOMPOK B DI TAMAN KANAK-KANAK DHARMA WANITA SIDOREJO 2 DESA SIDOREJO KECAMATAN GENENG KABUPATEN NGAWI - Anita Solihatul Wahidah; Anik Nurhayati (Kurikula : Jurnal Pendidikan, 2021)
ABSTRACT The crude motoric skills of a child are the process by which a person learns to skillfully move his limbs. The development of crude motor skills in TK Dharma Wanita Sidorejo is limited to the activity of streets, morning exercise, and ape limitations of the agency. Observed, researchers have found that children of group B (5-6 years of age) have not yet reached full levels according to standards of child attainments. The purpose of the study at TK Dharma Wanita Sidorejjo 2 Geneng Ngawi is 1) to find out the application of ape sensory paths in TK Dharma Wanita Sidorejo 2, 2) to identify the improvement of a child's rough motor skills through the application of ape sensory path. The research method employed by researchers is to use a qualitative approach with a qualitative type of descriptive research. The study was carried out in group B (ages 5-6). Data collection techniques in this study use observation, interview and documentation. As for the data analysis techniques, the reduction of data, the presentation of data and the drawing of conclusions. Studies indicate that: 1) the application of ape sensory path at TK Dharma Wanita Sidorejo 2 successfully attracted children to the activities of crude motor skills. 2) by using ape sensory paths children successfully to achieve rough motor skills Key Words: APE, Sensory Path, The crude motoric